Comparison of numerical methods and traditional ways of calculating safety factor for Al-Hawiz Dam (Journal of Hama University, 2019)
The aim of this study is to compare numerical methods and traditional ways of calculating safety factors for earth dam.The finite element method was chosen as one of the numerical methods and the Spencer method was chosen as a traditional way using the critical equations.This study was conducted on Al-Hawiz Dam and we studied the balance of both sides of the dam using the GEO-STUDIO software and two loading modes in both Spencer and the limited elements.The results obtained in each of the two methods having a consensus between safety factors in spencer method and finite element method because normal stress distribution The finite element method  each slide exists own safety factor and total safety factor for the slope while spencer method the safety factor has one value, and a number of suggestions and recommendations were proposed.